Sylloge Nummorum Graecorum, Brasil I. Museu Histórico Nacional, Rio de Janeiro. Moedas gregas e provínciais romanas - Rutter, Keith (Cadernos do LEPAARQ (UFPEL), 2014)
Abstract: The numismatic collection of the Museu Histórico Nacional in Rio de Janeiro is the largest in Brazil. It contains 131,000 specimens from all regions and historical periods, of which many are informatively and handsomely displayed in a permanent exhibition in the museum. This volume of the Sylloge Nummorum Graecorum, the first of a Brazilian collection, catalogues 1,750 of the coins that count as Greek. The descriptions and details of the coins are presented in the form that is usual for SNG volumes, with plentiful bibliographical referencing, in particular to other volumes of SNG. The catalogue is introduced by two essays: one, by the author Maricí Martins Magalhães on the development of the collection and the work of cataloguing it, the other by Professor Luiz Aranha Corrêa do Lago, curator of the permanent exhibition. The title of the exhibition is “As moedas contam a História” (Coins tell the [Hi]story), and Professor do Lago here provides for readers an authoritative account of the development of Greek coinage as it is extensively illustrated in the volume. In terms of chronological spread he is able to refer to coins from the very early days of coining in Asia Minor (nos. 1271-2, electrum and silver coins respectively of Lydia) right through to the later stages of the Roman provincial series in Alexandria (Maximianus Herculius, nos. 1726-37); the geographical spread covers an area running from the Straits of Gibraltar in the west to Afghanistan in the east.